Incorporación y evolución del principio de oportunidad en Colombia comparado con Estados Unidos (2017)
With the pass of time many cultures had been develop its own criminal systems according with the evolution of society. Many times, we could find different reconstructions of historical references that show us the system's main features that with time are enhancing and let us know the roots of our legislation. In the present article, it is pretended to enunciate one of the characteristics of that criminal system and its contribution to ours, making a parallel and studying the importance of pleadings in both criminal laws as fundamental part for an optimal enforcement. The pleadings were proposed by Constitutional level that pursue effectiveness of justice and relief the Colombiancriminal system